ANALISIS PELAKSANAAN KURIKULUM 2013 DALAM PEMBELAJARAN MATEMATIKA DI SMA SEKOTA BANDA ACEH - Afdhalil Ilyas (Universitas Syiah Kuala, 2019)
Abstract: The 2013 curriculum has been applied at all levels of education since the academic year of 2013/2014 to increase students knowledge, especially in mathematics. However, the implementation of the 2013 curriculum in learning faced many obstacles. It became a new challenge for teachers and students in implementing the learning. The implementation of the 2013 curriculum is a benchmark of the success of education in Indonesia. It places students as the center of learning. Students are directed to be able to understand the materials and solve problems in learning independently. The research problem was ‘what are the obstacles faced by teachers and students in implementing the 2013 curriculum?’. This study aimed to determine the implementation of the 2013 curriculum and examined the constraints faced by teachers and students in implementing the 2013 curriculum. The research subjects were three senior high schools in Banda Aceh. Data concerning the implementation of the 2013 curriculum were obtained from observations, interviews, student response questionnaires and documentation. The data were analyzed using percentages. The results informed that the ability of teachers in developing learning instruments using the 2013 curriculum was good; 2) the constraints faced by teachers and learners varied; 3) teacher responses to the implementation of the 2013 curriculum were varying; 4) the responses of students to the implementation of the 2013 curriculum in mathematics were positive (2.36).Keywords: Implementation of 2013 Curriculum, Mathematics Learning